Mapping Indonesian Department of Communication - Pratama, Bayu Indra (Penerbit Universiti Kebangsaan Malaysia, 2019)
The beginning of the history of communication studies in Indonesia is constructed by the invisible college of Indonesian scholars who returned from their studies in the United States, but no one has explained the contemporary conditions. Popular invisible college researches have tended to use co-citation and co-authorship analysis, even though invisible college relations are also formed through a scholarly background. The explanation about invisible colleges contributes to explaining influential groups in a particular field of science. Using social network analytics combined with historical reviews, this study explains the link between communication science education institutions in Indonesia that form an invisible college based on academic background identity. This study uses data relations between educational backgrounds and work places for 741 lecturers from 30 communication studies with ‘A’ accreditation in Indonesia. This study found that there was a shift in the orientation of communication science education from the USA to the local because of the development of communication science education in the ASEAN region, one of which was Indonesia. This study found that there were five invisible colleges based on the most influential educational backgrounds in communication science education namely the University of Indonesia, University of Padjadjaran, University of Gadjah Mada, University of Mercu Buana, and LSPR College of Communication. There are three factors making them the influential institutions: historical factors, heterogeneity, and geographical proximity.